(untitled) (Ushuluddin International Conference (USICON), 2019)
The treasure of thoughts in the history of Islamic civilization is very broad. However, little known by public in general. In the realm of academic in the period of recent century, we know many fresh ideas emerging in order to face global challenges. The thinkers surely hope his thoughts to be of benefit to society, as an alternative in dealing with rapid changes of the world. This research is intended to know how dissemination (da